Blue TiO2 Nanotube (b-TiO2) as a Support Material Electrode in a Photoelectrochemical Cell for Nitrogen Fixation - Muhammad Iqbal Syauqi; Gunlazuardi, Jarnuzi; Grandprix TM Kadja (Malaysian Journal of Science (MJS), 2025)
We have been developing an artificial photosynthesis device based on a photoelectrochemical cell to convert N2 to NH3 in a greener way as an alternative to the Haber–Bosch process, which requires high energy and releases a huge amount of CO2; this device consists of a dark cathode and photoanode. An electrode material that can absorb nitrogen and weaken its chemical bond is necessary for the dark cathode, while a photoanode material that can absorb visible light and have an intrinsic oxidation potential to split water is necessary. Currently, we are developing blue TiO2 (b-TiO2) and CoOx modified b-TiO2 for both electrode materials. b-TiO2 was synthesized by the electrochemical reduction of TiO2 nanotubes in aqueous solution, whereas TiO2 nanotubes were prepared using the electro-oxidation technique. The synthesized b-TiO2 exhibited a bandgap shift to 2.96 eV and an increase in conductivity owing to the presence of Ti3+ species. The addition of CoOx to b-TiO2 shifted the bandgap to 2.70 eV and increased its oxidative performance, as shown by the negative shift of the water oxidation onset potential and the 13.55% increase in RhB degradation under visible light and 500 mV external bias. Furthermore, when used in tandem as a dark cathode and photoanode, the device can convert N2 to NH3 up to 0.0063 µmol h−1 cm−1 without external bias and 0.0128 µmol h−1 cm−1 with 500 mV external bias.